Design and construction of a sliding garage door powered by a 3-phase motor controlled by a Variable Frequency Drive (VFD) based on an Outseal PLC, with a remote control as the trigger - Moody N. Tumembow; Franklin Bawano; Harry O. Wensen; Djefry P. Hosang (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
This study discusses the design and development of an automatic sliding garage door system powered by a three-phase electric motor and controlled via a Variable Frequency Drive (VFD) based on an Outseal Programmable Logic Controller (PLC). The system is engineered to enhance operational efficiency and convenience by utilizing a remote control as the primary trigger for opening and closing the door. Using a VFD enables flexible motor speed regulation, resulting in smoother, safer door movement. The Outseal PLC serves as the central controller, integrating signals from the remote control and automatically managing the operation of both the VFD and the three-phase motor. Testing results demonstrate that the system operates with fast response, stability, and reliability under various conditions. At a VFD frequency setting of 3 Hz, the motor runs at 90 rpm, achieving an open/close cycle time of 13 seconds. When the frequency is increased to 3.5 Hz, the motor speed rises to 105 rpm, reducing the cycle time to 11 seconds. Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation, and InfrastructureSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and Production